An interarrival hyperexponential machine interference with balking, reneging, state-dependent, spares, and an additional server for longer queues - Ragab Omarah Al-Seedy; Fawziah M. Al-Ibraheem (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to treat the analytical solution of the truncated interarrival hyperexponential machine interference queue: H2/M/1/m+Y/m+Y in case of two branches with the following concepts: balking, reneging, state-dependent, spares, and an additional server for longer queues. Our research treats the general case for the values of m and Y considering the discipline FIFO. And some special cases have been verified.